2012
DOI: 10.1155/2012/183745
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Calf Thymus DNA with the Ni(II) Complex of Sodium 1,4-Dihydroxy-9,10-Anthraquinone-2-Sulphonate: A Novel Method of Analysis Using Cyclic Voltammetry

Abstract: Hydroxy-9,10-anthraquinones are cheaper alternatives to anthracycline drugs. They closely resemble anthracycline drugs both from a structural and functional viewpoint. Electrochemical behavior of the Ni(II) complex (Na 2 [Ni(NaLH) 2 Cl 2 ]·2H 2 O) of sodium 1,4-dihydroxy-9,10-anthraquinone-2-sulphonate (NaLH 2 ), analogue of the core unit of anthracycline anticancer drugs, was studied at physiological pH using cyclic voltammetry. The Ni(II) complex of sodium 1,4-dihydroxy-9,10-anthraquinone-2-sulphonate underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Under the same experimental conditions, cyclic voltammetry of pure DNA showed that there was neither any cathodic nor anodic peak in the potential range 0.0 to −0.85 V, clearly indicating that pure DNA was electrochemically inert in the potential range on a glassy carbon electrode. Previous studies [25,26,34,35] also showed that CT DNA was electrochemically inactive at a glassy carbon electrode surface. To find the reversibility of the reduction of doxorubicin hydrochloride in the presence of DNA, a plot of the ratio of the anodic to cathodic peak current ( pa / pc ) versus the logarithm of scan rate (log v) (Figure 3) is considered which shows that the pa / pc ratio is less than unity for lower scan rates and it is almost unity at higher scan rates [32] clearly suggesting that the reduction is quasireversible at lower scan rates and it is reversible at higher scan rates.…”
Section: Electrochemical Reduction Of Doxorubicin Hydrochloridementioning
confidence: 89%
See 4 more Smart Citations
“…Under the same experimental conditions, cyclic voltammetry of pure DNA showed that there was neither any cathodic nor anodic peak in the potential range 0.0 to −0.85 V, clearly indicating that pure DNA was electrochemically inert in the potential range on a glassy carbon electrode. Previous studies [25,26,34,35] also showed that CT DNA was electrochemically inactive at a glassy carbon electrode surface. To find the reversibility of the reduction of doxorubicin hydrochloride in the presence of DNA, a plot of the ratio of the anodic to cathodic peak current ( pa / pc ) versus the logarithm of scan rate (log v) (Figure 3) is considered which shows that the pa / pc ratio is less than unity for lower scan rates and it is almost unity at higher scan rates [32] clearly suggesting that the reduction is quasireversible at lower scan rates and it is reversible at higher scan rates.…”
Section: Electrochemical Reduction Of Doxorubicin Hydrochloridementioning
confidence: 89%
“…In a previous DNA interaction study, Radi et al [35] carried out a similar ferricyanide experiment to establish that cyclic voltammetric behavior of their studied compound was not affected by addition of a very large excess of DNA and that decrease in peak current of the compound was due to interaction of the compound with DNA and not owing to adsorption. Results of DNA titration using cyclic voltammetry were analyzed by the method of nonlinear fitting [25,26]. To do so, the following compound-DNA equilibrium was considered [36][37][38][39]:…”
Section: Interaction Of Doxorubicinmentioning
confidence: 99%
See 3 more Smart Citations